Extracellular Adenosine Diphosphate Stimulates CXCL10-Mediated Mast Cell Infiltration Through P2Y1 Receptor to Aggravate Airway Inflammation in Asthmatic Mice - Gao, Yan-Yan; Gao, Zeng-Yan (Frontiers in Molecular Biosciences, 2021)
Asthma is an inflammatory disease associated with variable airflow obstruction and airway inflammation. This study aimed to explore the role and mechanism of extracellular adenosine diphosphate (ADP) in the occurrence of airway inflammation in asthma. The expression of ADP in broncho-alveolar lavage fluid (BALF) of asthmatic patients was determined by enzyme linked immunosorbent assay (ELISA) and the expression of P2Y1 receptor in lung tissues was determined by reverse transcription-quantitative polymerase chain reaction. Asthmatic mouse model was induced using ovalbumin and the mice were treated with ADP to assess its effects on the airway inflammation and infiltration of mast cells (MCs). Additionally, alveolar epithelial cells were stimulated with ADP, and the levels of interleukin-13 (IL-13) and C-X-C motif chemokine ligand 10 (CXCL10) were measured by ELISA. We finally analyzed involvement of NF-κB signaling pathway in the release of CXCL10 in ADP-stimulated alveolar epithelial cells. The extracellular ADP was enriched in BALF of asthmatic patients, and P2Y1 receptor is highly expressed in lung tissues of asthmatic patients. In the OVA-induced asthma model, extracellular ADP aggravated airway inflammation and induced MC infiltration. Furthermore, ADP stimulated alveolar epithelial cells to secrete chemokine CXCL10 by activating P2Y1 receptor, whereby promoting asthma airway inflammation. Additionally, ADP activated the NF-κB signaling pathway to promote CXCL10 release. As a “danger signal” extracellular ADP could trigger and maintain airway inflammation in asthma by activating P2Y1 receptor. This study highlights the extracellular ADP as a promising anti-inflammatory target for the treatment of asthma.